Salawah Wahidiyah in The Frame of Thareeqat in Indonesian Archipelago: Resistance in The Face of Perverse Fatwas in Tasikmalaya - Khamami Zada (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2017)
The relationship of power and resistance against it has been widely discussed as an intellectual discursive debates. However, resistance groups against the theological authority is off the debate. This paper analyses the resistance movement of Salawah Wahidiyah (SW) in the face of the erroneous fatwa by the Assembly of Indonesia Ulema (MUI). With the analysis of power relationships, knowledge, and resistance, this paper finds that SW is fighting against the misguided fatwa of Tasikmalaya MUI which is carried out as the majority of theological hegemony to defend the doctrine and amaliyah as well as to reject the deviating claim. This is all done to maintain the freedom to believe and practice the teachings of an inside democracy which guarantees and protects the right of religious freedom. Ironically, the resistance of SW in Tasikmalaya was not able to replicate the success of the Centre SW in conducting resistance against NU figures. SW Tasikmalaya failed to reconcile the differences of religious views with MUI. As a result, the motion of SW became limited because it is still stigmatized as deviant.